Demonstration of communication using neutrinos - Stancil, D.D.; Adamson, P.; Alania, M.; Aliaga, L.; Andrews, M.; del Castillo, C.A.; Bagby, L.; Bazo Alba, J.L.; Bodek, A.; Boehnlein, D.; Bradford, R.; Brooks, W.K.; et al. (World Scientific Publishing, 2012)
Beams of neutrinos have been proposed as a vehicle for communications under unusual circumstances, such as direct point-to-point global communication, communication with submarines, secure communications and interstellar communication. We report on the performance of a low-rate communications link established using the NuMI beam line and the MINERvA detector at Fermilab. The link achieved a decoded data rate of 0.1 bits/sec with a bit error rate of 1% over a distance of 1.035 km, including 240 m of earth.
Keywords: Neutrino; Detector; Line (geometry); Beam (structure); Neutrino detector; https://purl.org/pe-repo/ocde/ford#1.03.00